Association between toll-like receptor2 Arg677Trp and 597T/C gene polymorphisms and pulmonary tuberculosis in Zahedan, Southeast Iran - Naderi,Mohammad (2013)
BACKGROUND: It is well known that toll-like receptor 2 (TLR2) mediates responses of both innate and adaptive immunity to microbial pathogen, including mycobacteria. Single-nucleotide polymorphisms (SNPs) in the TLR2 gene that impair its function may be associated with the development of pulmonary tuberculosis (PTB). The aim of this study was to evaluate the possible association between TLR2 Arg677Trp and 597T/C polymorphisms and PTB in a sample of Iranian population. MATERIALS AND METHODS: This case-;control study was performed on 174 PTB and 177 healthy subjects. Tetra amplification refractory mutation system-polymerase chain reaction (TARMS-PCR) was used to detect the SNPs. RESULTS: There was no significant difference in the polymorphism of Arg677Trp of the TLR2 gene among PTB and control groups (p > 0.05). The results showed that there was a significant difference between case and control groups regarding 597T/C polymorphism (χ2 = 12.21, p = 0.002). The TC and CC genotypes were found to be associated with the risk of PTB (OR = 2.13, 95% CI = 1.25-;3.62, p = 0.005 and OR = 4.88, 95% CI = 1.56-;15.26, p = 0.007, respectively). CONCLUSION: Our data suggest that 597T/C polymorphism, but not Arg677Trp polymorphism, of the TLR-2 gene is a risk factor for susceptibility to PTB in a sample of Iranian population.